The Evaluation of Digital Readiness Concept: Existing Models and Future Directions - Nasution, Reza Ashari; Rusnandi, Linda Sendy Lediana; Qodariah, Elis; Arnita, Devi; Windasari, Nila Armelia (School of Business and Management Institut Teknologi Bandung, 2018)
Abstract. The development of digital technology has significantly changed the business landscape. The emergence of new business models provides a greater potential to become more profitable. Therefore, many companies tread the path towards transformation through the adoption and use of digital technologies to catch the opportunities. Unfortunately, many companies fail to understand that the use of digital technologies requires different preparations. One of them is the requirement of an adequate level of digital readiness. The measurement of digital readiness is hindered due to the absence of a reliable, valid and specific model in measuring this construct. As a result, in order to measure the digital readiness of their employees, many companies are applying the existing technology readiness models which can be found in the current literature. This paper aims to provide a viewpoint of the adequacy of existing models for digital readiness measurement with a conception that digital readiness is not only a perception of a digital as an independent object but also as an integrated object.Keywords: Digital technology, digital transformation, digital readiness, readiness model